Evaluation of indications of abdominal hysterectomy performed in Chattagong Medical College Hospital - Ishrat, Shakeela; Khan, MA Taher (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i2.3863 Journal of Chittagong Medical College Teachers' Association 2008: 19(2):7-11